Relations among questionnaire and experience sampling measures of inner speech: a smartphone app study - Alderson-Day, Ben; Fernyhough, Charles (Frontiers in Psychology, 2015)
Inner speech is often reported to be a common and central part of inner experience, but its true prevalence is unclear. Many questionnaire-based measures appear to lack convergent validity and it has been claimed that they overestimate inner speech in comparison to experience sampling methods (which involve collecting data at random timepoints). The present study compared self-reporting of inner speech collected via a general questionnaire and experience sampling, using data from a custom-made smartphone app (Inner Life). Fifty-one university students completed a generalized self-report measure of inner speech (the Varieties of Inner Speech Questionnaire, or VISQ) and responded to at least 7 random alerts to report on incidences of inner speech over a 2-week period. Correlations and pairwise comparisons were used to compare generalized endorsements and randomly-sampled scores for each VISQ subscale. Significant correlations were observed between general and randomly sampled measures for only 2 of the 4 VISQ subscales, and endorsements of inner speech with evaluative or motivational characteristics did not correlate at all across different measures. Endorsement of inner speech items was significantly lower for random sampling compared to generalized self-report, for all VISQ subscales. Exploratory analysis indicated that specific inner speech characteristics were also related to anxiety and future-oriented thinking.